Libraries: A Hub of Technology Enhanced Learning Space - Rajan , Sarita S.; Esmail , Mohamed (Research Highlights in Language, Literature and Education Vol. 3, 2023)
The present study explores how to make the defining technology of this century more accessible, appealing, and inviting a variety of users and learners to meet the technological demands. Skills evolve as technology advances, which is required for job readiness, productivity, research, and digital transformation. To provide the best user service, library staff must be technologically savvy in order to answer broadened technology questions such as computers, databases, and new media. . Rather than viewing technology as a threat, it should be embraced as a support system for information services, social networking, RSS, and weblogs, among other things. In the digital era, the concept of libraries as physical spaces is rapidly giving way to web-based servers. The needs and motivations of the past, present, and digital future shaped library innovations. The new generation is being born into technology, surrounded by an infinite number of digital devices, and they have high expectations for technology-driven library services. Universities and their libraries are well-positioned to provide a rich source of market information that can help resource-constrained start-ups to globalise their business operations. As one of the more important elements of the innovation ecosystem, knowledge-sharing can help start-ups to make data-driven, strategic decisions, rather than basing forward momentum on unreliable intuition.